Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
You should substitute each of the values in the domain for x in the f(x) equation and g(x) equation too. You do this until f(x)=g(x). Remember to only compare results from the same values in domain. Does this help? Let me know if you need any help. I could also help you solve it if you would post the equations for f(x) and g(x).
For -3, f(x)=3(-3)-4=-9-4=-13
g(x)=(-3)^2 -2=9-2=7 Not the answer since f(x) ≠g(x)
For -1, f(x)=3(-1)-4=-3-4=-7
g(x)=(-1)^2 -2=1-2=-1 Not the answer since f(x) ≠g(x)
For 0, f(x)= 3(0)-4=0-4=-4
g(x)=(0)^2 -2=0-2=-2 Not the answer since f(x) ≠g(x)
For 2, f(x)=3(2)-4=6-4=2
g(x)=(2)^2 -2= 4-2 =2 This is the answer since f(x)=g(x)
For 5, f(x)=3(5)-4=15-4=11
g(x)=(5)^2 -2=25-2=23 Not the answer since f(x) ≠g(x)
For -3, f(x)=3(-3)-4=-9-4=-13
g(x)=(-3)^2 -2=9-2=7 Not the answer since f(x) ≠g(x)
For -1, f(x)=3(-1)-4=-3-4=-7
g(x)=(-1)^2 -2=1-2=-1 Not the answer since f(x) ≠g(x)
For 0, f(x)= 3(0)-4=0-4=-4
g(x)=(0)^2 -2=0-2=-2 Not the answer since f(x) ≠g(x)
For 2, f(x)=3(2)-4=6-4=2
g(x)=(2)^2 -2= 4-2 =2 This is the answer since f(x)=g(x)
For 5, f(x)=3(5)-4=15-4=11
g(x)=(5)^2 -2=25-2=23 Not the answer since f(x) ≠g(x)
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.